Exploring the feasibility of SS316L fabrication via CMT-based WAAM: A Comprehensive study on microstructural, mechanical and tribological properties - Lone, Saboor Fayaz; Rathod, Dinesh Wasudeo; Ahmad, Sheikh Nazir (Mechanical Engineering for Society and Industry, 2024)
Additive manufacturing (AM) is revolutionizing production, enabling the customization of components for specific applications while promoting sustainable and on-demand manufacturing. This innovative method is especially valuable for producing intricate and custom parts from metallic materials like SS316L. Known for its excellent corrosion resistance and high strength, AISI 316L austenitic steel is widely utilized in aerospace, medical, automotive, and marine industries. This study explores the deposition of multi layered SS316L wall using the Cold Metal Transfer (CMT)-based Wire Arc Additive Manufacturing (WAAM) technique. The resultant multilayered wall exhibited seamless fusion devoid of macroscopic defects. A comprehensive analysis of its morphology, microstructure, mechanical properties, and tribological performance was conducted. Microstructural examination revealed a progression from fine equiaxed grains with ferrites in the lower sections to coarser columnar grains with acicular ferrites in the upper sections. Vickers microhardness and Charpy impact tests indicated a decline in hardness and impact energy from lower to upper sections. Uniaxial tensile tests demonstrated decreasing yield and ultimate tensile strengths, alongside significant ductility and toughness. The coefficient of friction and wear rate escalated with higher loads and from lower to upper sections, predominantly displaying abrasive wear mechanisms. These results validate the efficacy and durability of the SS316L CMT-based WAAM process in fabricating high-quality structures with tailored mechanical and tribological properties.